A conceptual and contemporary approach to the evolution of impartiality in community interpreting - Leticia Santamaria Ciordia (JoSTrans: The Journal of Specialised Translation)
This paper provides an overview of the profile of the interpreter in Public Services, highlighting his/her role as a cultural mediator along with a reconsideration of the principle of impartiality in relation to this particular role. In contrast to the Codes of Ethics that have traditionally advocated for the least invasive role when interpreting, a growing number of voices have suggested that impartiality and neutrality are utopian and unachievable goals and defend a more inclusive, participatory role. Greater visibility would help both users and providers gain better understanding of the interpreter's role. One of the main challenges that educators face in the context of incorporating ethics into the curriculum is the persistent gap between theory and practice in the discipline. An approach based on empathy and critical skills should be encouraged in student training, alongside establishing realistic rules from a multi-dimensional perspective based on daily practice. The article concludes outlining six conditions that should be met to ensure the recognition and standardisation of community interpreting.